The take-anywhere, do-anything display. - Romero, J.J (IEEE spectrum)
The paper presents a commercial LCD computer display (3Qi) produced by the Pixel Qi company that offers e-paper's power savings and readability in sunlight. Pixel Qi's first production display is a 10-inch screen with 1024 by 600 pixels in the full-color mode. It's the first LCD screen that's optimized for mobile computing, in which the most common activity is the reading of text-in e-mail, code, or on a Web site. In adequate light, you can easily read and write without wasting any battery power on the backlight.